Sie sind auf Seite 1von 82

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

α

m

 

2

2

v

 

Θ

 

2

2

ω

 

g m h

c

c x 2

2

 

c

t

2

2

ϕ

 

m = V ρdv

F = m g

F G ❄ ❄ ✘ ✘ ✘ ✘ S h s B ♥
F
G
✘ ✘ ✘ ✘ S
h s
B
F 1
l 1
l ✲

F G F 1 B

M (B) = F G l 1 F 1 l = 0

l 1 =

F 1

F G

l

l 1

F G S ❄ ✻ ✻ h ❄ ✻ F 2 ✲ ✛ ✲ l
F
G
S
h
F 2
l 1
l
2
✲ ✛
✛x δ
✘ ✘ ✘ ✘
B
l

α = arcsin( h )

l

M B = F 2 l cos α + l 2 F G = 0

F 2 l cos α

δ x = d

2

sin α

l 2 =

F 2

F G

l

cos α

1

h s tan α

❆ ❆ ❆ d ✻
❆ ❆ ❆
d

F

g

❆ ❆ ❆ ❆ ❆ ❆ ❆ ❆

✟ ✟ ✟ ✟ ✟

✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟ ✟

h

s

2

d

2

2 sin α

✟ ✟ ✟ ✟ ✟

✻

sin α

2 +

d

2

sin α

= h s

tan α + 1

cos α h s

h s =

sin α + d

2

2

1

tan α

N/m Nm/radiant

N/m Nm/radiant ⑦ M asse m ❄ F = 1 F = 1 ❄ δ δ

M asse m

F = 1

F = 1

δ

δ

δ =

1 l 3

3EJ

c = 1

δ = 3EJ

1 l 3

d l G A B M (B) = 1

B

A

M (B) = 1

M (B) = 1

ϕ =

1 l

G J T

J T = J p = π d 4

32

c T =

= G J T

1

l

ϕ

A E

c s = E A

E = 1 10 11 · · · 1.6 10 11 N/m 2

 

m

 

z, w

Balg

 

V 0 p 0 w

V = πd 4 2

w

p F R

F R = p πd 2

4

p V κ = const

κ κ = 1, 405

(p 0 + ∆p)(V 0 V ) κ = p 0 V

0

κ = const

(V 0 + ∆V ) κ

f(a + h) = f(a) +

h

1! f (a) + h 2! f (a) +

2

d

V (V κ ) = κ V κ1

.

.

.

(V 0 + ∆V ) κ V

κ

0

f(a)

+ −∆V κ−1 κ V 0 1 h f (a)
+ −∆V
κ−1
κ V
0
1
h f (a)

1!

(p 0 + ∆p)(V

κ

0

+ κV

0

κ1

(V )) = p 0 V

κ

0

= const

κ

p 0 V

0

p 0 V

κ V

0

κ1

κ

+ ∆pV

0

pV κ V

0

κ1

κ

= p 0 V

0

κ

p 0 V

0

p 0 V

κ V

0

κ1

κ

+ ∆pV

0

κ

= p 0 V

0

1

p = p 0 κ V

0

V

= p 0 κ

1 πd 2

V 0

4

w

πd 2

πd 2

4

F R = p 0 κV

0

4

1

c L

w

c L = κ p 0

V

0

πd 2

4

2

✻ ❄
❅ ❅ ❅ ❅ ❅ ◗ ◗ ◗ ❄ ❅
◗ ◗ ◗ ❄
◗ ◗

 

 

 

0.6 MN/m 2 1.1 MN/m 2 1.8 MN/m 2

k E k E = d h k E = 1 4 d 2 π
k E k E = d h k E = 1 4 d 2 π

k E

k E =

d h

k E = 1 4 d 2 π

d π h

=

d

4 h

A h

c st = A E

h

c dyn = c st k dyn

A s A

τ

= F

A

τ = γ G

γ

 

γ = w

 
 

s

w F

 
 

F

s

 

w

=

A G

 

 

c st = A G

 

s

c dyn = c st k dyn

r i r a M T τ r,ϕ r

M T =

r

τ r ϕ r dϕ dz

M T = r 2 τ rϕ 2 π

τ =

M T

2 r 2 π

γ

τ = γ G

γ =

dϕ

= r

= r

1

γ

τ

G

M T

dr

dϕ

dr

2 r 2 π

G = r

τ

G

dϕ

dr

=

M T

1

2 r 2 π

G dr

ϕ =

M T 2 π

G

1

r

r

i

ϕ =

a

1

2

dr =

M T

1

1

1

1

 

G

2

   

2

2

 

r

M T

1

r

1

 

a

1

r

a

r

i

4 π

G

2

r

2

 

i

2 π

c st = 4 π G

1

1

r

2

i

r

2

a

k dyn

c dyn = c st k dyn

M T = F D m

2

F D m i d

k dyn M T = F D m 2 F D m i d F F

F

F M T = F D m

2

M T = 1